TEACHING METHODOLOGY: MODERN APPROACHES TO EFFECTIVE EDUCATION - Zoxidova Muyassar, (TADQIQOTLAR, 2025)
Teaching methodology plays a crucial role in improving the quality of education and ensuring that learners achieve meaningful results. Modern educational approaches emphasize  student-centered  learning,  active  participation,  and  the  integration  of technology.  This  paper  discusses  the  key  principles,  methods,  and  benefits  of contemporary teaching methodologies, highlighting their importance for both teachers and students.